Clinical Utility of Combined Tissue and Plasma Next-Generation Sequencing in Patients With Advanced, Treatment-Naïve NSCLC - Helena Bote-de Cabo, MD; Marco Siringo, MD; Esther Conde, MD, PhD; Susana Hernández, PhD; Fernando López-Ríos, MD, PhD; Alicia Castelo-Loureiro, MD; Esther García-Lorenzo, MD; Javier Baena, MD-PhD; Mercedes Herrera, MD; Ana Belén Enguita, MD; Yolanda Ruano, PhD; Jon Zugazagoitia, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: Tissue and plasma-based next-generation sequencing (NGS) have complementary roles in patients with advanced NSCLC. Nevertheless, whether there is any added clinical value in combining both methods in the treatment of naïve patients remains unclear. Methods: We retrospectively collected clinical and genomic data from 275 patients with treatment-naïve advanced NSCLC who had undergone plasma-based NGS at diagnosis in our institution. We analyzed patient data in two separate cohorts, each assessed with a different plasma-based NGS method: cohort 1 (n = 127, Guardant360), and cohort 2 (n = 148, FoundationACT/FoundationOne Liquid CDx). Ninety-five patients (75%) in cohort 1 and 108 patients (73%) in cohort 2 underwent concurrent amplicon-based tissue NGS testing locally. Results: Forty-three patients in cohort 1 (34%) and 49 patients in cohort 2 (33%) harbored European Society for Medical Oncology Scale for Clinical Actionability of Molecular Targets (ESCAT) I or II targetable driver alterations. The addition of orthogonal biopsy (tissue to liquid, or liquid to tissue) offered no relevant clinical value in cases with ESCAT I or II targetable drivers already detected by one method. In contrast, adding orthogonal biopsy incremented the detection of ESCAT I or II targetable drivers not only in cases with uninformative testing (undetectable circulating tumor DNA, unavailable/inadequate tissue) but also in about 5% of the patients with seemingly informative but driver undetected molecular results. The prevalence of ESCAT I or II targetable drivers in plasma was significantly higher in patients with adenocarcinoma, 20 pack-year or less smoking history, and abdominal metastases. Conclusions: Our study suggests that the addition of sequential orthogonal biopsy should be considered whenever an ESCAT I or II targetable driver has not been detected by the initial method, including cases with seemingly informative molecular analysis.